Cigarette smoking in pregnancy - Celina Łepecka-Klusek; Anna Bogusława Pilewska-Kozak; Grażyna Stadnicka; Klaudia Pałucka (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2016)
Introduction. Smoking cigarettes is a major health and social-economical problem. It poses a threat to reproduction, parturition and the health of the baby. Aim. Illustrating the problem of smoking cigarettes by pregnant women on the basis of the review of the bibliography.             Brief description of the state of the art. This research demonstrates the epidemiology and the scale of the problem as well as the consequences of smoking during pregnancy taking into consideration the division into the parturition and the health of the baby. It also discusses women's awareness of the negative effects of such behaviours. Conclusion. The review of the bibliography indicates that smoking cigarettes by pregnant women is not uncommon. The scale of the problem is not easy to assess due to the fact that many of these women simply do not admit to it. The negative consequences of smoking during pregnancy are quite numerous and pertain to both the parturition and the state of the newborn as well as the health of the child at a later stage in its life. This calls for the need to shape anti-nicotine attitudes, especially in girls and women in the reproductive period.